OPTIMASI DIAMETER LAS TITIK MENGGUNAKAN METODE TAGUCHI PADA PROSES RESISTANCE SPOT WELDING ROBOTIK DI MESIN OTC DAIHEN - Roni, Komar; Imaduddien Ariefa; Rieky Handoko; Anton Harseno; Muhammad Nanang Adi Saputra; Sahal Ahmad Albab (Politeknik Negeri Semarang, 2025)
Robotic welding technology has become a key component in modern manufacturing, particularly in automotive industries, due to its ability to deliver consistent weld quality and improve efficiency. However, weld quality remains highly dependent on process parameters such as current (Ampere), voltage, electrode movement speed, and heat input. In the context of resistance spot welding (RSW), optimizing these parameters is essential to achieve ideal weld diameters and ensure joint integrity. Previous research has primarily focused on tensile strength, overlooking diameter as a crucial quality metric in precision manufacturing. This study addresses that gap by investigating the influence of four welding parameters—current, voltage, speed, and heat input—on weld diameter using the Taguchi method. An experimental design with L8 orthogonal array was implemented to reduce the number of trials while maintaining robust analysis. The quality characteristic